Distribuição espaço temporal do consumo residencial de água potável na cidade de Uberlândia-MG - Faleiros, Fernanda Endo (2017)
Water plays an essential role in human survival and development, but it is known that its distribution on the surface is not egalitarian, leading to a lack of supply needed to meet the demands of many regions of the planet. For a better management of urban water resources is necessary a better spatial and temporal understanding of consumption. Thus, the objective of the present research was characterize the residential water consumption in Uberlândia, MG city, temporally and spatially, using the techniques of time series and geostatistical. The analysis of time series is based on a series of water consumption of the residential economies in Uberlândia - MG city, from 2005 to 2015, the results indicated that there is no trend in the general series for the whole analyzed period but there is an annual seasonality. The model that best suits the series studied is the Simple Seasonal, being efficient to describe the data, emphasizing an influence of the precipitation and the educational campaigns in the preview of the model in the year of 2015. The geostatistical analysis is based in the series of residential water consumption in the city of Uberlândia, MG, from 2011 to 2015, where it is concluded that there is no trend in all the analyzed periods, rainy and dry, for all years, 2011 to 2015, and all adjusted without exponential model, with weak dependence, due to its high nugget effect, found in the semivariograms. In relation to its spatial distribution, it is observed to high consumption of residential water, in the central sector of the city and its bordering areas. And an increase in water consumption from 2011 to 2013 in the rainy season, with a reduction in the dry period of 2013 extending through 2014 with further increase in 2015, with apex in the dry period of 2015.